A case report of hyponatremia associated with maprotiline treatment - Stanković Žana B.; Pavlović Zorana Z.; Jovičić Milica J.; Žarković Miloš P. (Srpsko lekarsko drustvo, 2015)
Background: Maprotiline is a tricyclic antidepressant (sometimes classified as a tetracyclic antidepressant), which is predominantly a norepinephrine/noradrenaline reuptake inhibitor, commonly prescribed for depression. Aim: To present a female patient with depressive episode and occurrence of hyponatremia during the maprotiline treatment. Case Report: A 62-year-old female was diagnosed with depressive episode four years ago. She was treated ambulatory with maprotiline 50mg/day and bromazepam 6mg/ day, from local psychiatrist. The patients also used enalapril 2x10 mg/day, metoprolol 2x50 mg/day, nifedipine 5 mg/day and simvastatin 20 mg/day for treating hypertension and dyslipidemia. After about 12 months of maprotiline use she was hospitalized at the Endocrinology unit of a local hospital due to appearance of confusion, unstable walking, cramps, as well as an increase in blood pressure. Then diagnosed hyponatremia (serum sodium level-112 mmol/L), corrected (137 mmol/L) by using parenteral therapy. The patient continued to use maprotiline without consultation with her psychiatrist. After one year, the patient was hospitalized at the Endocrinology unit of tertiary level due to detailed re-examination because of recurrent hyponatramia (117 mmol/L), corrected (136 mmol/L) by ambulatory use of parenteral therapy at a local hospital. Water test load was used and the Syndrome of inappropriate antidiuretic hormone secretion was diagnosed. Insulin Tolerance Test showed preserved the integrity of the hypothalamic-pituitary-adrenal axis. Antidepressant mirtazapine (15 mg/ day) was introduced due to recurrence of depression. Gradual reduction of depressive symptoms was observed to mirtazapine. Antihypertensive therapy, restriction of fluid intake and dietary regimen were still applied. Serum sodium concentrations were in the normal ranges over the past 18 months. Conclusion: Serum sodium level should be measured before and during the therapy with any class of antidepressants, especially in those patients with increased risk of the hyponatremia occurrence.